Penegakan Hukum Pidana Terhadap Praktek Jual Beli Surat Keterangan Kesehatan Yang Dipalsukan Pada Masa Pandemi Covid-19 - Putri, Fira Hanasti; Pasalbessy, John Dirk; Hattu, Jacob (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: During the Covid-19 pandemic, one of the conditions for traveling outside the region or abroad is to have a health certificate obtained by carrying out a health check at the hospital, this is used by irresponsible people who sell COVID-19 free health certificates counterfeited to people in need.Purposes of the Research: This paper aims to determine the form of criminal law enforcement against the practice of buying and selling falsified health certificates during the Covid-19 pandemic.Methods of the Research: This method using normative legal research methods, namely research conducted by studying literature or literature study related to the problems at hand. Normative legal research is legal research made from literature, which is one of the library collections in the form of printed works such as text books, fiction books, reference books that are collected, processed and stored to be presented to users to meet informationneeds.Results of the Research: Based on the results of the research, it was found that the form of criminal law enforcement against the practice of selling falsified health certificates was subject to criminal sanctions, namely Article 263 of the Criminal Code (KUHP), namely letter forgery in general and made clear by Article 268 of the Criminal Code (KUHP). Criminal Law), namely falsifying a doctor's certificate.